La discusión sobre la formación de lideres intermedios. Fundamentos, aprendizajes y desafíos - Lorena Peñailillo; Sergio Galdames; Simón Rodriguez (Recherches en Éducation)
This paper develops the lessons and challenges derived from the implementation of training programs for middle leaders. These programas have been implemented during the years 2009 and 2010, in a joint effort between the area of education of a district of Chile, and the CRECE program at the Pontificia Universidad Católica de Valparaíso, Chile. The program is based on leadership training involves passing through several stages. The initial stages involves knowing the challenges of a leadership roles, understanding the school as an organization in continuos improvement and stability, and integrating knowledge and initial skills to influence other teachers. Thus emerges the role of a middle leader, distributing leadership, and as a collaborator, mediator and facilitator of organizational improvement processes. This article proposes that these training programs should consider executing a team with expertise in the subject and work experience in an educational context, generate a high coordination with decision makers at local levels, a design methodology for developing knowledge influence individual and group level. This paper focuses the discussion of this stage in the development of educational leadership.